A Rare Case of Primary Solid Intrarectal Dermoid - Singh, Onkar (Medknow Publications, 2011)
Primary rectal teratomas are rare and only few cases have been reported in the literature worldwide. These usually occur in females. These are usually cystic but very rarely solid variants may occur. We present a case of a solid intra-rectal dermoid arising primarily in rectum from postero-lateral wall. Excision biopsy was done per rectally. Histology revealed the presence of squamous epithelium, fat cells, hair follicles, cartilaginous material and columnar lining of glandular structures suggestive of mature teratoma. It is usually benign but may become malignant, therefore complete resection is advised.